Long-Term Results Of Treatment Of Acute Hematogenous Osteomyelitis Of Long Bones In Children - Belyalov Arsen Marlenovich , Rustemova Gulnara Alievna, Shamsiev Azamat Mukhiddinovich, Yusupov Shukhrat Abdurasulovich , Makhmudov Zafar Mamadzhanovich (Miasto Przyszłości, 2024)
Hematogenous osteomyelitis (HO) of long tubular bones is one of the complex and pressing problems of purulent surgery, requiring close attention from specialists in various fields of medicine and comprehensive continuous study. Bone inflammation has been known for a long time.